2018
DOI: 10.1007/s00726-018-2674-8
|View full text |Cite
|
Sign up to set email alerts
|

Proapelin is processed extracellularly in a cell line-dependent manner with clear modulation by proprotein convertases

Abstract: Apelin is a peptide hormone that binds to a class A GPCR (the apelin receptor/APJ) to regulate various bodily systems. Upon signal peptide removal, the resulting 55-residue isoform, proapelin/apelin-55, can be further processed to 36-, 17-, or 13-residue isoforms with length-dependent pharmacological properties. Processing was initially proposed to occur intracellularly. However, detection of apelin-55 in extracellular fluids indicates that extracellular processing may also occur. To test for this, apelin-55 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…C11P is the only Elabela/Toddler isoform detected under endogenous conditions by mass spectrometry on embryos containing APELA mRNA 10 . The presence of dibasic sites strongly suggests that the precursor would be processed by PCSK3 in a cell type‐dependent manner, as recently shown for proapelin 26 . In this context, we can speculate that the processing of Elabela/Toddler may, like that of apelin, differ between cell types, resulting in different isoform‐mediated biological effects.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…C11P is the only Elabela/Toddler isoform detected under endogenous conditions by mass spectrometry on embryos containing APELA mRNA 10 . The presence of dibasic sites strongly suggests that the precursor would be processed by PCSK3 in a cell type‐dependent manner, as recently shown for proapelin 26 . In this context, we can speculate that the processing of Elabela/Toddler may, like that of apelin, differ between cell types, resulting in different isoform‐mediated biological effects.…”
Section: Discussionmentioning
confidence: 52%
“…10 The presence of dibasic sites strongly suggests that the precursor would be processed by PCSK3 in a cell type-dependent manner, as recently shown for proapelin. 26 In this context, we can speculate that the processing of Elabela/Toddler may, like that of apelin, differ between cell types, resulting in different isoform-mediated biological effects. Longer Elabela/Toddler isoforms appear to be very potent apelin receptor agonists, whereas C11P seems to be a poor agonist of the apelin receptor.…”
Section: T a B L Ementioning
confidence: 99%
“…The distribution, function and processing of these specific isoforms have yet to be fully elucidated. APLN is expressed as a 77-amino acid precursor, preproapelin, which is further processed by tissue-specific proteases [7]. The longest secretable form is apelin-55 [8,9].…”
Section: Introduction 1 the Apelinergic Systemmentioning
confidence: 99%
“…ELA-21, which is one amino acid less than the expected furin cleavage site, has never been reported in degradation studies. Interestingly, apelin-55 also contain these di-arginine residues, and it was shown that proprotein convertase subtilisin/kexin 3 (PCSK3) cleaves immediately after these dibasic residues in the N-terminal to generate apelin-17 and apelin-13 [ 27 , 28 ]. Here, ELA-11 and ELA-22 were identified as fragments of ELA-32 generated in vitro in human plasma, but there was no evidence for the presence of ELA-21, either in the plasma or tissue homogenates.…”
Section: Discussionmentioning
confidence: 99%